Adults' Markers of Face Processing Are Present at Age 6 and Are Interconnected Along Development. (October 2018) - Mardo, Elite; Avidan, Galia; Hadad, Bat-Sheva
Recent studies on the development of face processing argue for a late, quantitative, domain-specific development of face processing, and face memory in particular. Most previous findings were based on separately tracking the developmental course of face perception skills, comparing performance across different age groups. Here, we adopted a different approach studying the mechanisms underlying the development of face processing by focusing on how different face skills are interrelated over the years (age 6 to adulthood). Specifically, we examined correlations within and between different categories of tasks: face domain-specific skills involving face recognition based on long-term representations (famous face), and short-term memory retention (Cambridge Face Memory Test), perceptual face-specific marker (inversion effect), global effects in scene perception (global–local task), and the perception of facial expressions. Factor analysis revealed that face identity skills have a similar pattern of interrelations throughout development, identifying two factors: a face domain-specific factor comprising adultlike markers of face processing and a general factor incorporating related, but nonspecific perceptual skills. Domain-specific age-related changes in face recognition entailing short- and long-term retention of face representations were observed, along with mature perceptual face-specific markers and more general perceptual effects predicting face perception skills already at age 6. The results suggest that the domain-specific changes in face processing are unlikely to result from developmental changes in perceptual skills driving face recognition. Instead, development may either involve improvement in the ability to retain face representations in memory or changes in the interactions between the perceptual representations of faces and their representations in long-term memory.